Single‐cell RNA‐seq reveals fate determination control of an individual fibre cell initiation in cotton (Gossypium hirsutum) - Qin, Yuan; Sun, Mengling; Li, Weiwen; Xu, Mingqi; Shao, Lei; Liu, Yuqi; Zhao, Guannan; Liu, Zhenping; Xu, Zhongping; You, Jiaqi; Ye, Zhengxiu; Xu, Jiawen; et al. (Plant biotechnology journal, 2022)
Summary Cotton fibre is a unicellular seed trichome, and lint fibre initials per seed as a factor determines fibre yield. However, the mechanisms controlling fibre initiation from ovule epidermis are not understood well enough. Here, with single‐cell RNA sequencing (scRNA‐seq), a total of 14 535 cells were identified from cotton ovule outer integument of Xu142_LF line at four developmental stages (1.5, 1, 0.5 days before anthesis and the day of anthesis). Three major cell types, fibre, non‐fibre epidermis and outer pigment layer were identified and then verified by RNA in situ hybridization. A comparative analysis on scRNA‐seq data between Xu142 and its fibreless mutant Xu142 fl further confirmed fibre cluster definition. The developmental trajectory of fibre cell was reconstructed, and fibre cell was identified differentiated at 1 day before anthesis. Gene regulatory networks at four stages revealed the spatiotemporal pattern of core transcription factors, and MYB25‐like and HOX3 were demonstrated played key roles as commanders in fibre differentiation and tip‐biased diffuse growth respectively. A model for early development of a single fibre cell was proposed here, which sheds light on further deciphering mechanism of plant trichome and the improvement of cotton fibre yield. With scRNA‐seq, cotton fibre cell was identified differentiated at −1 DPA. It further refines the spatiotemporal patterns of two command genes, MYB25‐like and HOX3, who determine fibre differentiation and tip‐biased diffuse growth respectively.